A Suitable Thermal Stress Index for the Elderly in Summer Tropical Climates. (2017) - Chindapol, Sumavalee; Blair, John; Osmond, Paul; Prasad, Deo
Abstract: The elderly are particularly vulnerable to heatwaves and this research investigates the degree of thermal stress they experience and identifies a suitable index, using Thailand as the case study location. Several global heat stress indices were evaluated for their ability to predict thermal stress in the tropics: Universal Thermal Climate Index (UTCI), Heat Stress Index (HSI), Tropical Summer Index (TSI), Wet-bulb Globe Temperature Index (WBGT) and Discomfort Index (DI). The UTCI, WBGT and DI group tropical conditions in the zone of greater thermal stress, while the HSI and TSI are clustered in the lower stress categories and are more similar to the thermal sensation vote (TSV) and thermal comfort vote (TCV) definitions. Most indices correlated with the TSV, while only HSI and WBGT show a correlation with TCV. The research concluded that the HSI is the most suitable thermal stress index, although it still does not completely explain tropical heat stress conditions.